Should Patients with Deep Vein Thrombosis Alone be Treated as Those with Concomitant Asymptomatic Pulmonary Embolism? A Prospective Study - Monreal, Manuel; Büller, Harry; Lensing, Anthonie Wa; Bonet, Montserrat; Roncales, Javier; Muchart, Jordi; Fraile, Manuel (Thrombosis and Haemostasis, 2002)
The established initial treatment of patients with deep vein thrombosis (DVT) or pulmonary embolism (PE) consists of the administration of subcutaneous, weight adjusted, low-molecular weight heparin (LMWH). However, the use of the same LMWH dosages for patients with either DVT or PE is not supported by data from comparative studies.1,000 consecutive patients with acute, proximal DVT were prospectively evaluated. All patients underwent a ventilation-perfusion lung scan on admission, and remained in hospital for at least 7 days. Patients with silent PE received once daily 10,000 to 15,000 IU subcutaneous LMWH dalteparin according to body weight for 7 days, and then vitamin K antagonists. Patients with DVT alone received LMWH in a fixed dose of 10,000 IU once daily for at least 5 days, and then vitamin K antagonists. The rate of both, major bleeding and symptomatic PE episodes during the 7-day study period was evaluated.Thirteen patients (1.3%) developed recurrent PE (1 died) and 16 patients (1.6%) had major bleeding (7 died). Recurrent PE was significantly more common in patients with silent PE (9 of 258 patients, 3.5%) than in those with DVT alone (4 of 742 patients, 0.5%. Odds ratio: 6.5; p <0.001). There were no significant differences in bleeding rate between patients with silent PE and those with DVT alone. However, the use of a fixed 10,000 IU dose in patients with DVT alone led to a significantly lower bleeding rate in patients weighing over 70 kg: 1 of 349 patients (0.3%) as compared to 9 of 393 patients (2.3%) in those weighing less than 70 kg (odds ratio: 0.12; p = 0.018).Fixed-dose 10,000 IU of LMWH dalteparin once daily proved to be both effective and safe in patients with DVT alone. The observed recurrence rate of 0.5% in these patients compares favourably with the 3.5% rate in patients with silent PE. Furthermore, this fixed-dosage was also safe. Patients weighing over 70 kg had a significant decrease in the rate of major bleeding, and no compensatory increase in the rate of recurrent PE.
Keywords: Venous thrombosis; pulmonary embolism; anticoagulant therapy; recurrences; bleeding